Implications of trade policy changes for the competitiveness of Ecuadorian banana exports to the EU market - Giovanni Anania (International Centre for Trade and Sustainable Development (ICTSD), 2011)
Bananas have been some of the most sensitive goods in the negotiations on regional trade agreements between the European Union (EU) and the Andean countries, as well as those between the EU and Central American countries. As the largest exporter, Ecuador plays a critical role in setting world prices for the fruit. The EU, on the other hand, as the largest importer of bananas drives demand. An agreement between these two parties is likely to have significant impacts on the world market for bananas and the related development challenges ...
Keywords: 330